Neurophysiological localisation of ulnar neuropathy at the elbow: Validation of diagnostic criteria developed by a taskforce of the Danish Society of clinical neurophysiology. Issue 11 (November 2017) - Pugdahl, K.; Beniczky, S.; Wanscher, B.; Johnsen, B.; Qerama, E.; Ballegaard, M.; Benedek, K.; Juhl, A.; Ööpik, M.; Selmar, P.; Sønderborg, J.; Terney, D.; et al.
Highlights: Danish criteria for ulnar neuropathy at elbow (UNE) have high specificity (98.4%) and positive predictive value (95.2%). Specificity for UNE is higher in the Danish criteria compared to the AANEM criteria. Danish criteria for UNE are Z-score based and thus useful across centres and clinical settings. Abstract: Objective: This study validates consensus criteria for localisation of ulnar neuropathy at elbow (UNE) developed by a taskforce of the Danish Society of Clinical Neurophysiology and compares them to the existing criteria from the American Association of Neuromuscular and Electrodiagnostic Medicine (AANEM). The Danish criteria are based on combinations of conduction slowing in the segments of the elbow and forearm expressed in Z-scores, and difference between the segments in m/s. Examining fibres to several muscles and sensory fibres can increase the certainty of the localisation. Methods: Diagnostic accuracy for UNE was evaluated on 181 neurophysiological studies of the ulnar nerve from 171 peer-reviewed patients from a mixed patient-group. The diagnostic reference standard was the consensus diagnosis based on all available clinical, laboratory, and electrodiagnostic information reached by a group of experienced Danish neurophysiologists. Results: The Danish criteria had high specificity (98.4%) and positive predictive value (PPV) (95.2%) and fair sensitivity (76.9%). Compared to the AANEM criteria, the Danish criteria had higher specificity ( p  < 0.001) and lower sensitivity ( p  = 0.02). Conclusions: The Danish consensus criteria for UNE are very specific and have high PPV. Significance: The Danish criteria for UNE are reliable and well suited for use in different centres as they are based on Z-scores.